Lentinus punjabensis (Polyporaceae), a new species from Lal Suhanra National Park, southern Punjab, Pakistan - Asif, Muhammad; Saba, Malka; Maula, Fazli; Raza, Mubashar (Phytotaxa, 2024)
Lentinus punjabensis, from the biodiverse Lal Suhanra National Park in southern Punjab, Pakistan, is the first new species of Lentinus for the country. It is characterized by an applanate pileus with a dark brown depressed center, erect scales, decurved margins, eroded lamellae, oblong to sometimes lacrymoid basidiospores, clavate to lageniform or sometimes lacrymoid cheilocystidia, and the presence of a dimitic hyphal system in the pileipellis. Our study presents the taxonomic position, using morphology, and molecular characterization, based on phylogenetic analyses of ITS and 28S sequences, to prove the distinctiveness of the new species. We provide an illustrated morphological description and comparison with morphologically similar or phylogenetically related species. In addition, we provide a key to the known species of Lentinus in Pakistan.